Robust estimation of (partial) autocorrelation. (31st March 2015) - Dürre, Alexander; Fried, Roland; Liboschik, Tobias
Abstract The autocorrelation function (acf) and the partial autocorrelation function (pacf) are elementary tools of linear time series analysis. The sensitivity of the conventional sample acf and pacf to outliers is well known. We review robust estimators and evaluate their performances in different data situations considering Gaussian scenarios with and without outliers as well as times series with heavy tails in a simulation study. WIREs Comput Stat 2015, 7:205–222. doi: 10.1002/wics.1351 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.